(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the study of methods and techniques of forming language competence of future specialists in the process of Ukrainian language learning (for professional purposes). It has been determined that effective mastery of language culture is an integral part of professional activity and ensures successful communication, competitiveness and professional development of specialists in modern conditions on the labor market. An analysis of scientific sources on the concept of ‘communicative competence’ has been conducted and approaches to its understanding have been outlined. The article examines in detail effective methods and techniques that contribute to the development of students’ language competence. Among them, special attention is paid to: the method of situational modeling, project-based learning, interactive technologies, linguostylistic analysis of texts, the case method and digital technologies. The importance of exercises focused on various specialties that ensure the integration of language knowledge into the professional activities of students has been separately highlighted. It has been noted that the use of such methods allows not only to form language skills, but also to develop communicative competence necessary for effective interaction in a professional environment. Special emphasis has been placed on the use of interactive approaches that contribute to the active involvement of students in the educational process and the formation of their speech culture. The importance of introducing modern digital technologies into the educational process, which allow diversifying teaching methods and increasing their effectiveness, has been emphasized. Thus, the formation of language competence of future specialists occurs through a combination of traditional and modern educational methods that contribute not only to the development of language knowledge, but also provide a comprehensive approach to professional communication. This emphasizes the importance of improving the methods of teaching the Ukrainian language for professional purposes in higher education institutions.